An Outbreak of Typhoid Fever in Florida Associated with an Imported Frozen Fruit - Katz, Dolores J.; Cruz, Miguel A.; Trepka, Mary Jo; Suarez, Juan A.; Fiorella, Paul D.; Hammond, Roberta M. (The Journal of infectious diseases, 2002)
An outbreak of typhoid fever in Florida involving at least 16 persons during the winter of 1998-99 was investigated using case-control, environmental, and laboratory methods. The genomic profiles of Salmonella serovar Typhi (Salmonella Typhi) isolates from the 15 confirmed case subjects were identical. Consumption of fruit shakes made with frozen mamey, a tropical fruit, was significantly associated with illness (matched odds ratio, 7.6; 95% confidence interval, 1.4–81.4). Laboratory testing showed that the fruit was heavily contaminated with fecal coliforms; no Salmonella Typhi was isolated. The frozen mamey was prepared in plants in Guatemala and Honduras. No further cases occurred after the frozen product was recalled. As our nation’s food sources become increasingly globalized, the risk of outbreaks of exotic diseases linked to contaminated imported food will increase. This outbreak highlights the need for new approaches to ensure the safety of our food supply